PPARα inhibition modulates multiple reprogrammed metabolic pathways in kidney cancer and attenuates tumor growth - Abu Aboud, Omran (Am J Physiol Cell Physiol, 2015)
Kidney cancer [renal cell carcinoma (RCC)] is the sixth-most-common cancer in the United States, and its incidence is increasing. The current progression-free survival for patients with advanced RCC rarely extends beyond 1–2 yr due to the development of therapeutic resistance. We previously identified peroxisome proliferator-activating receptor-α (PPARα) as a potential therapeutic target for this disease and showed that a specific PPARα antagonist, GW6471, induced apoptosis and cell cycle arrest at G(0)/G(1) in RCC cell lines associated with attenuation of cell cycle regulatory proteins. We now extend that work and show that PPARα inhibition attenuates components of RCC metabolic reprogramming, capitalizing on the Warburg effect. The specific PPARα inhibitor GW6471, as well as a siRNA specific to PPARα, attenuates the enhanced fatty acid oxidation and oxidative phosphorylation associated with glycolysis inhibition, and PPARα antagonism also blocks the enhanced glycolysis that has been observed in RCC cells; this effect did not occur in normal human kidney epithelial cells. Such cell type-specific inhibition of glycolysis corresponds with changes in protein levels of the oncogene c-Myc and has promising clinical implications. Furthermore, we show that treatment with GW6471 results in RCC tumor growth attenuation in a xenograft mouse model, with minimal obvious toxicity, a finding associated with the expected on-target effects on c-Myc. These studies demonstrate that several pivotal cancer-relevant metabolic pathways are inhibited by PPARα antagonism. Our data support the concept that targeting PPARα, with or without concurrent inhibition of glycolysis, is a potential novel and effective therapeutic approach for RCC that targets metabolic reprogramming in this tumor.